Feeding device for plastic processing - CHEN DONG; YANG MENGLAN (2024)
The utility model discloses a feeding device for plastic processing, which belongs to the technical field of plastic processing and comprises a supporting component, the supporting component is connected with a conveying component through a connecting component, a collecting component is arranged outside the conveying component, the conveying component is connected with a driving component through a transmission component, and the driving component is connected with a crushing component. According to the crushing device, materials are poured into the crushing assembly, the conveying assembly is controlled to work, the working conveying assembly drives the crushing assembly to rotate through the transmission assembly and the driving assembly, and the rotating crushing assembly performs crushing operation on the materials falling on the rotating crushing assembly; the crushed materials move into the conveying assembly and then move towards the end away from the transmission assembly, and dust and dirt mixed in